2020
DOI: 10.3389/fonc.2020.01070
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Breast Lesions Between Deep Learning-Based Computer-Aided Diagnosis System and Experienced Radiologists: Comparison the Performance Between Symptomatic and Asymptomatic Patients

Abstract: The purpose of this study was to compare the diagnostic performance of breast lesions between deep learning-based computer-aided diagnosis (deep learning-based CAD) system and experienced radiologists and to compare the performance between symptomatic and asymptomatic patients. Methods: From January to December 2018, a total of 451 breast lesions in 389 consecutive patients were examined (mean age 46.86 ± 13.03 years, range 19-84 years) by both ultrasound and deep learning-based CAD system, all of which were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These accurate category decreases assisted by the CAD model avoid unnecessary biopsies and reduce the medical costs and psychological burden of patients ( 24 ). Xiao et al demonstrated that CAD could improve the diagnostic performance of experienced radiologist and subsequently prevent the unnecessary biopsy of 54.76% of benign lesions ( 39 ); Choi et al also found that CAD could assist radiologists in correctly reclassifying BI-RADS 3 or 4a nodules ( 40 ). Conversely, an agreement rate (68/147, 46.26%) with pathology was obtained in those increases from category 3 to 4a or above.…”
Section: Discussionmentioning
confidence: 99%
“…These accurate category decreases assisted by the CAD model avoid unnecessary biopsies and reduce the medical costs and psychological burden of patients ( 24 ). Xiao et al demonstrated that CAD could improve the diagnostic performance of experienced radiologist and subsequently prevent the unnecessary biopsy of 54.76% of benign lesions ( 39 ); Choi et al also found that CAD could assist radiologists in correctly reclassifying BI-RADS 3 or 4a nodules ( 40 ). Conversely, an agreement rate (68/147, 46.26%) with pathology was obtained in those increases from category 3 to 4a or above.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a few breast imaging studies explored the potential to downgrade BI-RADS 4 patients using predictive models, including AI-based algorithms. Works by Wang et al ( 23 ), Zhao et al ( 24 ) and Xiao et al ( 25 ) assessed a commercially available AI tool for breast ultrasound to downgrade category 4A cases to category 3. In the Wang et al, out of 43 category 4A studies, 14 were correctly downgraded.…”
Section: Discussionmentioning
confidence: 99%